Inovasi Pelayanan Pajak Melalui Samsat Digital Nasional Di Unit Pelaksana Teknis Pendapatan Daerah Wilayah I Palu - Zaharani, Vilza; Hattab, Syahruddin; Astuti, Agusta Sri (JPS: Journal of Publicness Studies, 2024)
This study aims to determine the Innovation of Tax Services through National Digital Samsat in the Regional Revenue Technical Implementation Unit of Region I Palu. The research method used is Descriptive Qualitative, which provides an overview of the phenomenon or focus of the problem being studied that occurs at the research location according to existing facts. The data collection techniques used are observation, in-depth informant interviews and documentation to collect the data needed in the form of primary data and secondary data. While the informants in this study amounted to 7 people, namely 3 people from the UPT. Regional Revenue of Region I Palu, 2 people who use the National Digital Samsat application and 2 people who use manual samsat services. The theory used in this study is the theory of Everett M. Rogers where there are five indicators used in Tax Service Innovation through National Digital Samsat in the Regional Revenue Technical Implementation Unit of Region I Palu. The five indicators are: Relative Advantage, Compatibility, Complexity, Triability, Observability. Based on the results of the study, it shows that Tax Service Innovation Through National Digital Samsat has been running well on indicators of relative profit and suitability. While on the indicators of complexity, the possibility of trying, and the ease of observability have not gone well. This can be seen from the fact that there are still people who experience difficulties, namely disruptions in the system that hinder transactions and people's ability to understand a technology, not the trial phase of the National Digital Samsat (SIGNAL) application directly to taxpayers in Central Sulawesi and the socialization carried out is not optimal, because there are still many people who do not know about tax payment innovations through the SIGNAL application,and the quality of the system that is still experiencing problems when making tax payments Online. All forms of this problem need improvement so that in the future it can run well.